Influence of SOFTWOOD‐fillers content on the biodegradability and morphological properties of WOOD–polyethylene composites. Issue 1 (27th January 2016) - Tazi, M.; Erchiqui, F.; Kaddami, H.
Abstract : In the present work, wood flour reinforced thermoplastic polymer composites, with and without coupling agents, were prepared by melt processing, and their mechanical and thermal behaviors were analyzed. For preparation of polymer composites, six different formulations were used. On the other side, the degradation of wood fillers up to 97 days and water uptake in composites up to 10 weeks was evaluated, respectively, using fungi specie ( Gloephyllyllum trabeum ) and water absorption tests. To study the morphological changes resulting from microorganism activity, scanning electron microscopy was used. The obtained results indicate that the addition of wood fillers to the polyethylene matrix increases the degree of crystallinity, and tensile strength. On the contrary, resistance to fungi decay and water absorption decrease as a function of the wood fillers content thus the composite becomes more vulnerable to moisture uptake and micro‐organism attack, which can change the morphological and mechanical strength of composite. Based on the obtained results, microorganisms mainly affect the surface of composite and the adhesion of wood and polymer matrix. An optimized amount of filler content can reinforce the polymeric matrix more efficiently while decrease the rate of degradation of wood fillers as well. POLYM. COMPOS., 39:29–37, 2018. © 2016 Society of Plastics Engineers